2020
DOI: 10.1155/2020/8834758
|View full text |Cite
|
Sign up to set email alerts
|

Fractal Characteristics of Pores in the Longtan Shales of Guizhou, Southwest China

Abstract: The pore structure of marine-continental transitional shales from the Longtan Formation in Guizhou, China, was investigated using fractal dimensions calculated by the FHH (Frenkel-Halsey-Hill) model based on low-temperature N2 adsorption data. Results show that the overall D 1 (fractal dimension under low relative pressure, P / … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…The sufficient pore volume and larger surface area is effective for the substantial gas adsorption and gas storage, whereas the availability of a good pore networking and fractals are beneficial for gas transportation (Zhang et al, 2016;Huang et al, 2020). Likewise, the FHH plots of the studied samples indicate that shales have two separate fractal dimensions at different pressure ranges (low-pressure and high-pressure divisions), and the pore surface (D 1 ) is rough/rugged(Fig.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The sufficient pore volume and larger surface area is effective for the substantial gas adsorption and gas storage, whereas the availability of a good pore networking and fractals are beneficial for gas transportation (Zhang et al, 2016;Huang et al, 2020). Likewise, the FHH plots of the studied samples indicate that shales have two separate fractal dimensions at different pressure ranges (low-pressure and high-pressure divisions), and the pore surface (D 1 ) is rough/rugged(Fig.…”
Section: Discussionmentioning
confidence: 81%
“…11) implying fractals in low-and highpressure range that leads to the ruggedness of pore surfaces and complex pore structures together (Chen et al, 2019). Similarly, two types of fractal dimensions have also been observed in the Longtan Shales (Middle Permian) of Guizhou, Southwest China (Huang et al, 2020), and Early Permian coal beds of West Bokaro, Jharkhand, India (Mendhe et al, 2017b).…”
Section: Discussionmentioning
confidence: 94%
“…This indicates that as the grain size increases, the difference in particle shape has a more obvious impact on the pore structure. It is widely acknowledged that the determination of the fractal dimension plays an important role in predicting the physical and mechanical properties of geomaterials [45,46]. Huang et al [45] quantified the fractal characteristics of the pore structure of shale and found a significant relationship between the fractal dimension and permeability.…”
Section: Effect Of Grain Size On the Microsrcture's Fractal Dimensionmentioning
confidence: 99%
“…It is widely acknowledged that the determination of the fractal dimension plays an important role in predicting the physical and mechanical properties of geomaterials [45,46]. Huang et al [45] quantified the fractal characteristics of the pore structure of shale and found a significant relationship between the fractal dimension and permeability. Kong et al [47] established a fractal model of pore size distribution for porous geomaterials based on the fractal characteristics of pores, which could be used to study hydraulic properties.…”
Section: Effect Of Grain Size On the Microsrcture's Fractal Dimensionmentioning
confidence: 99%
“… 8 In the Guizhou Longtan Formation, Huang et al examined the relationship between permeability and pores in marine and continental transitional shales. 9 To examine how different shale is from one another, Wang et al used SEM digital images, fractal and multifractal theory, and shale samples. 10 Using field emission scanning electron microscopy (FE-SEM), gas adsorption, and helium porosity measurements, Yang et al studied the pore structure of organic-rich shale.…”
Section: Introductionmentioning
confidence: 99%